Effect of previous treatment upon fattening gains of heifers-Summary. - Richardson, D.; Smith, E.F.; Cox, R.F. (Kansas Agricultural Experiment Station, 2011)
The way that animals are fed and managed before going into the feed lot may influence the rate and efficiency of gain on a fattening ration. This is particularly true with pigs. This experiment was planned to obtain information on the response of heifers on a fattening ration after having received different kinds of roughage in their wintering rations. The different rations were supplemented to make them similar in protein, total digestible nutrients, vitamins, and minerals.
Keywords: Beef; Gains; Heifers